2013
DOI: 10.3747/pdi.2012.00272
|View full text |Cite
|
Sign up to set email alerts
|

Bariatric Surgery in a Patient on Peritoneal Dialysis

Abstract: COrreSPONDeNCe gastrectomy. We believe that our patient's case will help convince surgeons and nephrologists to continue PD in such patients, as is already being reported in other types of abdominal surgeries (14,15).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…Valle et al were the first to report a case series of pre-transplant laparoscopic metabolic surgery in 5 people on peritoneal dialysis in 2012 (163). Imam et al reported a case of laparoscopic VSG in a 27-year old male on peritoneal dialysis for 3.6 years which did not require perioperative interruption of peritoneal dialysis (164). No perioperative surgical complications occurred and the patient was able to resume his pre-operative dialysis regimen after 4 weeks.…”
Section: Does the Feasibility Of Metabolic Surgery Differ With Dialysmentioning
confidence: 99%
“…Valle et al were the first to report a case series of pre-transplant laparoscopic metabolic surgery in 5 people on peritoneal dialysis in 2012 (163). Imam et al reported a case of laparoscopic VSG in a 27-year old male on peritoneal dialysis for 3.6 years which did not require perioperative interruption of peritoneal dialysis (164). No perioperative surgical complications occurred and the patient was able to resume his pre-operative dialysis regimen after 4 weeks.…”
Section: Does the Feasibility Of Metabolic Surgery Differ With Dialysmentioning
confidence: 99%
“…The publication by Valle et al 4 demonstrated the immediate postoperative continuation of PD, observing 1 patient who underwent laparoscopic gastric banding and 4 who underwent laparoscopic Roux-en-Y gastric bypass. The 2013 letter by Imam et al 5 also illustrated this point in a patient who had a laparoscopic sleeve gastrectomy. Laparoscopic sleeve gastrectomy, laparoscopic Roux-en-Y, and laparoscopic gastric banding are 3 widely popular and effective weight loss surgeries.…”
Section: Discussionmentioning
confidence: 95%
“…The 2013 letter by Imam et al. 5 also illustrated this point in a patient who had a laparoscopic sleeve gastrectomy. Laparoscopic sleeve gastrectomy, laparoscopic Roux-en-Y, and laparoscopic gastric banding are 3 widely popular and effective weight loss surgeries.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Bariatric surgery has been successfully performed in PD patients without interruption of PD, depending on the procedure 49,50 . Elective sleeve gastrectomy has been performed laparoscopically with resumption of low‐volume supine exchanges on postoperative day 2 in one case report, 49 followed by gradual increases in his final fill after 2 weeks and resumption of the presurgery regimen after 4 weeks. Valle et al, described successful resumption of PD within 48 hours of laparoscopic Roux en Y gastric bypass in three patients 50 .…”
Section: Management Of Pd When Other Abdominal Procedures Are Performedmentioning
confidence: 99%